A study on the job satisfaction of professional librarians doing support staff duties in libraries within the University of the Philippines - Santos, Paul L.; Lapuz, Elvira B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
A total of 41 respondents were surveyed from 22 libraries within the university. The questionnaire was based after the one prepared by Gonda and was modified to suit the objectives of the study. Data regarding professional and support staff duties were all retrieved from the University's REPS PES form and was used as reference material for the job satisfaction part of the survey questionnaire.
An ordinary library user would find it hard to distinguish a professional librarian from a support staff in normal circumstances. Although a simple misconception between position titles seem trivial, it means a lot especially for librarians whose lifeblood was concentrated in an effort to excel in the field of librarianship. To know whether they mind doing support staff duties and being wrongly labeled by other professional fields in a venture that needs closer inspection. As such, the study focused on determining the job satisfaction of professional librarians working within the University of the Philippines Diliman and verifying which duties and responsibilities are being shared with support staff. All unit and departmental libraries within U.P. Diliman were included in the study.
Recommendations included the increase of overall budget of departmental and unit libraries as well as the addition of support staff, the importance of intra-personal skills as a requirement for professional librarians, the strict implementation of job descriptions for both support staff and professional librarians and finally the continuity of the university's training regimen for developing the skills and knowledge base of its librarians.
The data gathered from the survey questionnaires and interviews revealed that (a) majority of the respondents (46.3%) belong to the age bracket 51 and above; (b) twelve (29.3%) respondents hold the position title of College Librarian II; (c) an overwhelming majority (97.6%) of the respondents have permanent status for their jobs; (d) thirteen of the respondents (31.7%) are working in the access/public/readers services; (e) a large number (61%) of the respondents have rendered more than fifteen years of library service within the university; (f) thirty-four (82.9%) of the respondents indicated that they personally applied for the job; (g) The special skills and abilities of the respondents ranked according to highest yielded mean are 1) human relations skills, 2) supervising skills, 3) administrative skills, 4) computing or typing skills and 5) oral and written communication skills; h) the library activity on which the respondents obtained the highest mean (3.61%) is "answers reference questions and other queries"; (i) the statement which yielded the highest mean value (5.51%) in terms of job satisfaction is" I answer reference questions and other queries whenever possible"; (j) the following activities both shared by professional librarians and support staff are 1) answers directional questions and/or phone calls, 2) explains library rules and regulations, 3) reviews/recalls and monitors the use of library materials, 4) shelf-reading, 5) sorting and shelving of library materials; and k) there were no negative comments based on interviews and factual data with regard to professional librarians performing support staff duties.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman Libraries; Librarians -- Job descriptions; Librarians -- Job satisfaction